Perspective: Disentangling the effects of tES on neurovascular unit - Arora, Yashika; Dutta, Anirban (Frontiers in Neurology, 2023)
Transcranial electrical stimulation (tES) can modulate the neurovascular unit, including the perivascular space morphology, but the mechanisms are unclear. In this perspective article, we used an open source ‘rsHRF toolbox’ and an open-source functional magnetic resonance imaging (fMRI) transcranial direct current stimulation (tDCS) data set to show the effects of tDCS on the temporal profile of the hemodynamic response function (HRF). We investigated the effects of tDCS in the grey matter and at three regions of interest in the grey matter underlying the anodal electrode (FC5), cathodal electrode (FP2), and an independent site remote from the electrodes (PZ). A ‘canonical HRF’ with time & dispersion derivatives and a Finite Impulse Response (FIR) model with three parameters captured the effects of anodal tDCS on the temporal profile of the HRF. The FIR model showed tDCS onset effects on the temporal profile of HRF for verum and sham tDCS conditions that were different from the no tDCS condition, which questions the validity of the sham tDCS (placebo). Here, we postulated that the effects of tDCS onset on the temporal profile of HRF are subserved by the effects on neurovascular coupling. We provide our perspective based on previous work on tES effects on the neurovascular unit, including mechanistic grey-box modelling of the effects of tES on the vasculature that can facilitate model predictive control (MPC). Future studies need to investigate online effects of tES on the neurovascular unit that can facilitate MPC tES dose-response to address the momentary (“state”) and phenotypic (“trait”) factors.